2006
DOI: 10.1037/1040-3590.18.4.393
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent and predictive validity of the Psychopathy Checklist: Youth version across gender and ethnicity.

Abstract: The concurrent and predictive validity of the Psychopathy Checklist: Youth Version (PCL:YV) were examined across gender and ethnicity using multiple outcome measures on a community-based sample of 130 adjudicated youths. The PCL:YV demonstrated concurrent validity with externalizing behavior problems but, it is important to note, was also associated with internalizing measures of negative affect. With a mean follow-up period of 3 years, the PCL:YV was found to predict general and violent recidivism in male, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
84
1
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(94 citation statements)
references
References 55 publications
6
84
1
3
Order By: Relevance
“…Intraclass correlation coefficients range from .82 to .98 (Andershed et al, 2007;Cauffman et al, 2009;Das et al, 2009;Forth et al, 2003). PCL:YV scores are also correlated with externalizing psychopathology, violence, antisocial behaviour, and recidivism (Kosson et al, 2002;Kubak & Salekin, 2009;Murrie et al, 2004;Salekin, 2008;Salekin et al, 2004;Schmidt et al, 2006;Vitacco et al, 2006;2010).…”
Section: Methodsmentioning
confidence: 99%
“…Intraclass correlation coefficients range from .82 to .98 (Andershed et al, 2007;Cauffman et al, 2009;Das et al, 2009;Forth et al, 2003). PCL:YV scores are also correlated with externalizing psychopathology, violence, antisocial behaviour, and recidivism (Kosson et al, 2002;Kubak & Salekin, 2009;Murrie et al, 2004;Salekin, 2008;Salekin et al, 2004;Schmidt et al, 2006;Vitacco et al, 2006;2010).…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, modest associations of around .30 were found between psychopathic traits and total number of incidents in young adults imprisoned for crimes committed as juveniles (Edens, Poythress, & Lilienfeld, 1999), in male juvenile offenders in a residential training facility (Brandt, Kennedy, Patrick, & Curtin, 1997), in a judicial assessment facility (Hicks, Rogers, & Cashel, 2000), and in a residential treatment program for dually diagnosed offenders (Rogers, Johansen, Chang, & Salekin, 1997). During the last few years, research into adolescent psychopathy in relation to recidivism is increasing (e.g., Edens, Campbell, & Weir, 2007;Schmidt, McKinnon, Chattha, & Brownlee, 2006). A meta-analysis across 21 adolescent samples has shown a significant association between psychopathy and general, as well as violent, recidivism in adolescents (mean weighted effect sizes of .24 and .25, respectively).…”
Section: Introductionmentioning
confidence: 97%
“…19 In a meta-analysis of 21 studies, 15 of them focusing exclusively on males, the PCL-YV or the PCL-Revised 19 for adults predicted general and violent recidivism, more strongly among men than women. 20 Other studies of adolescents have shown that the PCL-YV predicted violent and nonviolent criminal convictions among males and weakly or not at all among females, 21,22 and violent behaviour. 23,24 We found only one study 23 examining PCL-YV predictions after controlling for CD and it showed that the PCL-YV continued to predict future violent offending among adolescent males.…”
mentioning
confidence: 99%